2005
DOI: 10.1080/00016480510012291
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical and stereological study of glucocorticoid receptors in rat medial vestibular nucleus neurons and the effects of unilateral vestibular deafferentation

Abstract: Using immunocytochemistry and stereology, we found that the majority of MVN neurons expressed glucocorticoid receptors, but there were no significant differences in the number of glucocorticoid receptor-expressing neurons in the ipsilateral or contralateral MVNs at 10 h or 2 weeks post-UVD; furthermore, corticosterone levels did not vary significantly between the UVD and control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…In this study, the acute labyrinthine dysfunction was occurred in all rats at the 1st day after UL and static symptoms partially disappeared at the 3rd day after UL. The observations of animals’ behaviors, after UL, were in agreement with the previous report [33]. The mGluRs have been reported to be involved in long term potential and LTD.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the acute labyrinthine dysfunction was occurred in all rats at the 1st day after UL and static symptoms partially disappeared at the 3rd day after UL. The observations of animals’ behaviors, after UL, were in agreement with the previous report [33]. The mGluRs have been reported to be involved in long term potential and LTD.…”
Section: Resultssupporting
confidence: 92%
“…The rest gel out of these trimmed target bands was abandoned. Comparisons between UL and sham groups were always made on the same gels and all of the assays were repeated to confirm their accuracy [33,52,53]. Then, the target proteins in the trimmed SDS gel were transferred onto PVDF membranes using a transblotting apparatus (Bio-Rad, Hercules, CA, USA) for 1.5 h (mGluR2, 98 kDa; mGluR7, 102 kDa) in transfer buffer containing 20% methanol, 1.5% glycine, and 0.3% Tris-base.…”
Section: Methodsmentioning
confidence: 99%
“…We found that corticosterone levels were similar between BVD and sham rats, suggesting that the BVD rats were not abnormally stressed. These results are consistent with those from our previous studies 26–29 . This does not rule out the possibility that humans with BVD have high circulating glucocorticoid levels.…”
Section: Animal Studies Of the Emotional Effects Of Vestibular Impairsupporting
confidence: 92%
“…No longterm studies have been carried out in patients with chronic bilateral vestibular loss. Several studies of UVD and BVD in rats and guinea pigs have found no long-term changes in either glucocorticoid levels or their receptors (Gliddon et al, 2003;Lindsay et al, 2005;Russell et al, 2006;Zhang et al, 2005Zhang et al, , 2008. Vertigo artificially induced in control subjects by caloric irrigation of the external auditory canal has been shown to cause an increase in cortisol levels (Daglias et al, 2005); however, it is unknown whether this has any effect on cognition.…”
Section: Why Should Manipulation Of the Vestibular System Have Effectmentioning
confidence: 99%